ANALISIS PENDEKATAN MARKETING PUBLIC RELATIONS DALAM PENGEMBANGAN PROMOSI PARIWISATA DI KOTA BOGOR - Shafia Aqsha Nuraini; Roni Jayawinangun; Imani Satriani (Jurnal Penelitian Sosial Ilmu Komunikasi, 2020)
This study aims to find out how the Bogor Tourism and Culture Office, especially the Promotion section, runs its activities and programs to develop promotions on the tourism sector in Bogor City. The research uses qualitative research methods, Case Study. The process of data collection was carried out by conducting interviews with sources of the Bogor Tourism and Culture Office which act as Key Informants and Informants, and sources from the Ministry of Tourism Republic of Indonesia act as triangulation. The result of this study is the emergence of a development of tourism promotion in the Bogor City for audiences through an assessment of the media that has been used as a promotional tool using SWOT analysis techniques. Where the assessment was obtained from a program that had been carried out by the Bogor City Tourism and Culture Office which was categorized by using 3 Marketing Public Relations Strategies namely pull, push and pass. So that in the end these activities and developments had an impact on the increasing number of visitors who came to Bogor City. Keywords: Bogor city; marketing public relations; promotion; SWOT; tourism